Co-delivery of small molecule hedgehog inhibitor and miRNA for treating liver fibrosis. (January 2016) - Kumar, Virender; Mondal, Goutam; Dutta, Rinku; Mahato, Ram I.
Abstract: In liver fibrosis, secretion of growth factors and hedgehog (Hh) ligands by hepatic parenchyma upon repeated insults results in transdifferentiation of quiescent hepatic stellate cells (HSCs) into active myofibroblasts which secrete excessive amounts of extracellular matrix (ECM) proteins. An Hh inhibitor GDC-0449 and miR-29b1 can play an important role in treating liver fibrosis by inhibiting several pro-fibrotic genes. Our in-silico analysis indicate that miR-29b1 targets several profibrotic genes like collagen type I & IV, c-MYC, PDGF-β and PI3K/AKT which are upregulated in liver fibrosis. Common bile duct ligation (CBDL) resulted in an increase in Ptch-1, Shh and Gli-1 expression. miR-29b1 and GDC-0449 were co-formulated into micelles using methoxy poly(ethylene glycol)-block-poly(2-methyl-2-carboxyl-propylene carbonate-graft-dodecanol-graft-tetraethylenepentamine) (mPEG-b-PCC-g-DC-g-TEPA) copolymer, and injected systemically into CBDL mice. High concentrations of GDC-0449 and miR-29b1 were delivered to liver cells as determined by in situ liver perfusion at 30 min post systemic administration of their micelle formulation. There was a significant decrease in collagen deposition in the liver and serum injury markers, leading to improvement in liver morphology. Combination therapy was more effective in providing hepatoprotection, lowering liver injury related serum enzyme levels, reducing fibrotic protein markers such as collagen, α-SMA, FN-1 and p-AKT compared to monotherapy. In conclusion, inhibition of Hh pathway and restoration of miR-29b1 have the potential to act synergistically in treating CBDL-induced liver fibrosis in mice. Graphical abstract: